BET 3: Bedside ultrasound for the diagnosis of sternal fracture. Issue 12 (23rd November 2015) - Racine, Samuel; Drake, David
Abstract : A shortcut review was carried out to establish whether ultrasound is an effective diagnostic tool for the diagnosis of sternal fractures. 27 papers were found of which 4 presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. The clinical bottom line is that in patients with blunt thoracic injury and suspected isolated sternal fracture, ultrasound seems superior to conventional radiology to diagnose sternal fracture.